Challenges and Sustainability of China’s Socio-Economic Stability in the Context of Its Demographic Development - Andrea Čajková; Peter Čajka (Societies, 2021)
Like many developed countries in the world, China currently faces many serious demographic challenges that pose a potential risk to the country’s socio-economic development and stability. The current demographic development and trend is characterized by a change in the reproductive behavior of the population, characterized by a decline in birth rates, a change in family behavior, and a shift in the value system. This paper is aimed at identifying the impact of population policy and the degree of its influence on both the economic and social system of the country. Based on a deterministic approach, the findings reveal and demonstrate the serious demographic challenges facing China, and we are noting that there is no guarantee that parametric adjustments, such as shifting the retirement age, will de facto ensure the financial health of the pension system by preventing bankruptcy. We point out the risks and prospects for the sustainability of China’s socio-economic development based on an analysis of past and current Chinese demographic policy.